2009
DOI: 10.1002/art.24965
|View full text |Cite
|
Sign up to set email alerts
|

Increased tibiofemoral cartilage contact deformation in patients with anterior cruciate ligament deficiency

Abstract: Objective. To investigate the in vivo cartilage contact biomechanics of the tibiofemoral joint following anterior cruciate ligament (ACL) injury.Methods. Eight patients with an isolated ACL injury in 1 knee, with the contralateral side intact, participated in the study. Both knees were imaged using a specific magnetic resonance sequence to create 3-dimensional models of knee bone and cartilage. Next, each patient performed a lunge motion from 0°to 90°of flexion as images were recorded with a dual fluoroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
152
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(168 citation statements)
references
References 48 publications
(83 reference statements)
12
152
4
Order By: Relevance
“…Experimental studies by Bingham et al [58], Li et al [59], and Van de Velde et al [60] using biplane X-ray images of subjects in a full-extension weight-bearing position have showed that the contact centroids lie anterior to the anterior-posterior (AP) midline of the cartilage for both the lateral and medial compartments. Contact centroid estimation by the DSX-based model in the current study was consistent with those previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies by Bingham et al [58], Li et al [59], and Van de Velde et al [60] using biplane X-ray images of subjects in a full-extension weight-bearing position have showed that the contact centroids lie anterior to the anterior-posterior (AP) midline of the cartilage for both the lateral and medial compartments. Contact centroid estimation by the DSX-based model in the current study was consistent with those previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…One in vivo study has shown that the ratio of the medial to lateral contact area was 1.35 at 30 of flexion under nonweight-bearing conditions in healthy subjects (5). Van de Velde et al (20) estimated the in vivo tibiofemoral contact area based on matching dual fluoroscopy images to MR images during a single-leg quasistatic lunge. They reported that healthy subjects have a medial to lateral tibiofemoral contact area ratio of %1.55 between 0 and 15 of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the contact areas were measured directly in this study, instead of estimating the cartilage interference (19,20) based on the MR image acquired from different positions. Recent studies using segmented MR images have shown that MRI assessment of cartilage contact area is a valid method (12) and comparable to the pressure-sensitive film technique (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15] Combination of MR imaging and double fluoroscopy on knees during motion and various flexion angles show similar results (in healthy subject [16][17][18][19] and in subjects with torn cruciate ligaments [19][20][21] ). On the contrary, gaps among the joint surfaces are a common observation in knee arthroscopic operations.…”
Section: -3mentioning
confidence: 69%